1980
DOI: 10.1093/sjaf/4.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Paulownia—A Crop Tree for Wood Products and Reclamation of Surface-Mined Land

Abstract: Paulownia, a naturalized Asiatic species, has been widely planted in the southeastern United States as a shade and ornamental tree because of its rapid growth and beautiful flowers. Although its multiple-use properties have made it an important commercial wood in Japan, it has not been used commercially in the United States. Recently, increased demand for paulownia from Japanese wood industries has created a potential new market for U.S. production of the species. The botanical characteristics, habitat conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The finding at Site 2 in the current study that Paulownia clones differed significantly in dry mass confirmed a similar finding by Berdón Berdón et al [13]. The high-volume production of Paulownia species is accompanied by wood lightness that is second only to balsa among timber species, but the wood is much stronger than balsa [3,16]. Other desirable wood attributes including ability to maintain original dimensions when exposed to moisture and lower susceptibility to burning by virtue of high temperature required to cause burning make Paulownia a quality timber for engineering purposes [13].…”
Section: Productivitysupporting
confidence: 91%
See 1 more Smart Citation
“…The finding at Site 2 in the current study that Paulownia clones differed significantly in dry mass confirmed a similar finding by Berdón Berdón et al [13]. The high-volume production of Paulownia species is accompanied by wood lightness that is second only to balsa among timber species, but the wood is much stronger than balsa [3,16]. Other desirable wood attributes including ability to maintain original dimensions when exposed to moisture and lower susceptibility to burning by virtue of high temperature required to cause burning make Paulownia a quality timber for engineering purposes [13].…”
Section: Productivitysupporting
confidence: 91%
“…Steud.] has received the most attention in the United States [14,15] because it has been naturalized in the southeastern part of the country for over 150 years [16]. Our focus turned to P. elongata S.Y.…”
Section: Introductionmentioning
confidence: 99%
“…Leaves and flowers of Paulownia have medicinal uses and are rich in nitrogen, serving as good fertilizer and fodder (Zhu et al, 1986 [2] ). Its tolerance to drought and soil extremes has made it commercially impor-tant for use in reclamation of surface-mined land (Tang et al, 1980 [3] ). Recently, there has been increased interest in this genus because of its potential use in reforestation of nutrientpoor soils (Marcotrigiano and Jagannathan, 1988 [4] ).…”
Section: Bapmentioning
confidence: 99%
“…The stem cuttings are generally more difficult to propagate than the root cuttings. However, difficulties associated with root cutting propagation also exist and these may include physical damage to the root epidermis and cortex, decay due to high temperatures and attack by pathogenic organisms (Tang et al, 1980 [3] ). Additionally, none of these traditional propagation methods is suitable for generating large amounts of planting material of selected elite trees.…”
Section: Bapmentioning
confidence: 99%
“…Its leaves and flowers show medicinal properties and can also be used as fodder and fertilizers due to their high nitrogen concentration [5]. Its tolerance to drought and soil extremes makes it commercially important for use in the reclamation of surfacemined land [6]. It is also a suitable raw material for pyrolysis conversion into liquid and gaseous products [7].…”
Section: Introductionmentioning
confidence: 99%